2006
DOI: 10.1016/j.vaccine.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel live recombinant mycobacterial vaccine against bovine tuberculosis more potent than BCG

Abstract: Mycobacterium bovis infection of cattle and other domesticated animals exacts a significant economic toll in both economically developing and industrialized countries. Vaccination of herds and/or wild animals that share their grazing land and serve as reservoirs of infection has been proposed as a strategy to combat bovine tuberculosis. However, the only currently available vaccine, M. bovis BCG, is not highly efficacious. Here we show that a live recombinant vaccine, rBCG30, which expresses large amounts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…It was further demonstrated that M. smegmatis and M. bovis BCG strains that were modified to overexpress immunogenic antigens targeted by the autophagy-lysosome pathway (such as Ag85B) led to an increase in antigen presentation ( Jagannath et al, 2009). This is in agreement with a different study showing that a live BCG strain overexpressing Ag85B is a more efficient vaccine when compared with the wildtype BCG strain (Horwitz et al, 2006). DNA vaccines used directly or as prime-boost are alternative promising approaches to either improve the efficacy of the current BCG vaccine or to create a new more effective one (Rivas-Santiago and Cervantes-Villagrana, 2014).…”
Section: Arg677trp (C2029t)supporting
confidence: 84%
“…It was further demonstrated that M. smegmatis and M. bovis BCG strains that were modified to overexpress immunogenic antigens targeted by the autophagy-lysosome pathway (such as Ag85B) led to an increase in antigen presentation ( Jagannath et al, 2009). This is in agreement with a different study showing that a live BCG strain overexpressing Ag85B is a more efficient vaccine when compared with the wildtype BCG strain (Horwitz et al, 2006). DNA vaccines used directly or as prime-boost are alternative promising approaches to either improve the efficacy of the current BCG vaccine or to create a new more effective one (Rivas-Santiago and Cervantes-Villagrana, 2014).…”
Section: Arg677trp (C2029t)supporting
confidence: 84%
“…6B and D). These results for BCG are consistent with previous studies from this laboratory showing that immunization with BCG fails to elicit a strong DTH response to the 30-kDa protein (23,25,26), which all commonly used BCG strains produce in relatively small amounts (Fig. 1C and D) (22).…”
supporting
confidence: 92%
“…rBCG(mbtB)30 expresses r30 at a similar level to that in rBCG30, the highly potent recombinant BCG vaccine we previously developed (22,(24)(25)(26), and was made safer than BCG for immunocompromised persons by specifically engineering the strain to undergo limited replication in vivo. This was achieved by deletion of mbtB, resulting in a strain that cannot synthesize the mycobactin and exochelin molecules that are needed by mycobacteria for the acquisition of iron under low-iron conditions, such as occurs at sites of mycobacterial replication in the host (10,42).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by the fact that intraperitoneal anti-CD4 ϩ antibody treatment abrogates the protective effects of rCPAFϩIL-12 vaccination (33a). A similar approach using bacillus Calmette-Guérin (Mycobacterium bovis BCG) expressing the Mycobacterium tuberculosis 30-kDa major secretory protein has been shown to induce more robust protective immunity than BCG alone induces against subsequent challenge with virulent organisms (21). The results of our study provide further support for using secreted products as candidate vaccines for intracellular bacteria.…”
Section: Discussionsupporting
confidence: 53%